Direct silylation of Trypanosoma brucei metabolites in aqueous samples and their GC-MS/MS analysis - Podolec, Peter; Szabó, Alexandra Hengerics; Blaško, Jaroslav; Kubinec, Róbert; Górová, Renáta; Višňovský, Jozef; Gnipová, Anna; Horváth, Anton; Bierhanzl, Václav; Hložek, Tomáš; Čabala, Radomír (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2014)
A simple two-step method for the derivatization of polar compounds (lactate, alanine, glycerol, succinate and glucose) using hexamethyldisilazane (HMDS) and N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) was developed. This method allows direct derivatization of aqueous samples wihout sample pretreatment. The method was used for the analysis of the metabolites of the unicellular organism Trypanosoma brucei. The limits of detection by GC-MS/MS analysis were in the range of 0.02 mg L(-1) for glucose to 0.85 mg L(-1) for lactate.
Keywords: Aqueous samples; Protozoa; Organosilicon Compounds; trimethylsilylové sloučeniny; Lactic Acid; organické sloučeniny křemíku; kyselina mléčná; Reproducibility of Results; GC–MS/MS analysis; reprodukovatelnost výsledků; limita detekce; Trypanosoma brucei brucei; glukosa; plynová chromatografie s hmotnostně spektrometrickou detekcí; Trimethylsilylation; Glucose; Trimethylsilyl Compounds; Gas Chromatography-Mass Spectrometry; Limit of Detection; alanin; Metabolites; Alanine